Label-free, high content screening using Raman microspectroscopy: the toxicological response of different cell lines to amine-modified polystyrene nanoparticles (PS-NH2). Issue 18 (23rd August 2017) - Efeoglu, Esen; Maher, Marcus A.; Casey, Alan; Byrne, Hugh J.
Abstract : Raman microspectroscopy as a 'high content nanotoxicological screening technique' with the aid of multivariate analysis, on non-cancerous and cancerous cell lines. Abstract : Nanotoxicology has become an established area of science due to growing concerns over the production and potential use of nanomaterials in a wide-range of areas from pharmaceutics to nanomedicine. Although different cytotoxicity assays have been developed and are widely used to determine the toxicity of nanomaterials, the production of multi-parametric information in a rapid and non-invasive way is still challenging, when the amount and diversity of physicochemical properties of nanomaterials are considered. High content screening can provide such analysis, but is often prohibitive in terms of capital and recurrent costs in academic environments. As a label-free technique, the applicability of Raman microspectroscopy for the analysis of cells, tissues and bodily fluids has been extensively demonstrated. The multi-parametric information in the fingerprint region has also been used for the determination of nanoparticle localisation and toxicity. In this study, the applicability of Raman microspectroscopy as a 'high content nanotoxicological screening technique' is demonstrated, with the aid of multivariate analysis, on non-cancerous (immortalized human bronchial epithelium) and cancerous cell-lines (human lung carcinoma and human lung epidermoid cells). Aminated polystyrene nanoparticles are chosen as model nanoparticles due to their well-established toxic properties and cells were exposed to the nanoparticles for periods from 24–72 hours. Spectral markers of cellular responses such as oxidative stress, cytoplasmic RNA aberrations and liposomal rupture are identified and cell-line dependent systematic variations in these spectral markers, as a function of the exposure time, are observed using Raman microspectroscopy, and are correlated with cellular assays and imaging techniques.